2012
DOI: 10.1017/s1751731111001959
|View full text |Cite
|
Sign up to set email alerts
|

Ileal digestibility of amino acids of cassava, sweet potato, cocoyam and erythrina foliages fed to growing pigs

Abstract: Ileal digestibility in growing pigs fed starch-based diets with inclusion of four tropical leaves in a meal form was studied in a 5 3 5 Latin square design. Five diets were formulated with only casein as protein source in the basal diet (CAS), and casein plus dry cassava (CA) leaves, casein plus dry sweet potato (SP) leaves, casein plus dry cocoyam (CO) leaves and casein plus erythrina (ER) leaves in the other four diets. All diets contained the same amount of CP (14%), either provided by only CAS or a combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…A recent research on pigs, which compared ileal digestibility of amino acids using a diet comprised of 25% fresh sweet potato leaves versus a control diet with casein as the only protein source, concluded that sweet potato leaves could only replace a fraction of the protein typically derived from a more expensive plant-based source, such as soybeans, because of high fiber content and the presence of compounds that decreased amino acid digestibility. However, sweet potato leaves are still potentially quite useful as a protein-supplement for pigs in the tropics where there is a close association between local feed sources, local crops, and animals-small-scale, mixed-farming systems (REGNIER et al, 2012;REGNIER et al, 2013). Nguyen reported that ensiling the leaves resulted in a higher digestibility of nutrients compared to drying the leaves (NGUYEN et al, 2012).…”
Section: Potential Use Of Leaves and Vinesmentioning
confidence: 99%
“…A recent research on pigs, which compared ileal digestibility of amino acids using a diet comprised of 25% fresh sweet potato leaves versus a control diet with casein as the only protein source, concluded that sweet potato leaves could only replace a fraction of the protein typically derived from a more expensive plant-based source, such as soybeans, because of high fiber content and the presence of compounds that decreased amino acid digestibility. However, sweet potato leaves are still potentially quite useful as a protein-supplement for pigs in the tropics where there is a close association between local feed sources, local crops, and animals-small-scale, mixed-farming systems (REGNIER et al, 2012;REGNIER et al, 2013). Nguyen reported that ensiling the leaves resulted in a higher digestibility of nutrients compared to drying the leaves (NGUYEN et al, 2012).…”
Section: Potential Use Of Leaves and Vinesmentioning
confidence: 99%
“…Les fanes de cultures énergétiques duales Ce sont des coproduits fibreux de certains fruits et tubercules amylacés disponibles après leur récolte et/ ou prélevés tout au long du cycle de végétation. Ils sont principalement consommés par les ruminants mais des travaux récents ont été consacrés à leur évaluation pour l'alimentation du porc (Kambashi et al, 2014 ;Régnier et al, 2012Régnier et al, , 2013Leterme et al, 2005Leterme et al, , 2012, (cf. encadré 1 qui résume les principes d'utilisation de ces ressources pour le porc).…”
Section: Figure 2 Principales Les Légumineuses à Graines Produites (unclassified
“…Over two 10-day periods, 6 pigs received a nitrogen-free diet in order to determine endogenous AA losses. The nitrogen-free diet was fed only at the end of the experiment in order to overcome the possible consequences of feeding a nitrogen-free feed on subsequent health and metabolism (Ré gnier et al 2012). At the conclusion of each sampling time, samples were thawed and mixed by individual animal, and a subsample was collected for chemical analysis.…”
Section: Sample Collection and Processingmentioning
confidence: 99%